The Efficiency of Titanium-Graphite Electrode Cells in the Presence of Ionic Liquids and Deep Eutectic Solvents as Electrolytes - Hasan, Bassam; Ali, Taghried; Kadim, Asmaa (Al-Nahrain Journal of Science, 2024)
Prior to the start of production, several factors must be considered, including the price, effectiveness, and environmental friendliness of batteries. Ionic liquids and deep eutectic solvents have shown significant success when employed as electrolytes with Titanium-graphite cells, especially when combined with additives that enhance their conductivity by reducing the high viscosity of these liquids. Evaluating the discharge voltage of the AlCl3-chloroacetamide IL with DCM as an additive revealed a voltage of 1.16V and an internal resistance of 11 Ohm. These electrochemical cells exhibited an intriguing response. Otherwise, when utilizing CaCl2.2H2O: Acetamide DES with DI water as an additive, the cell voltage measured 0.97V, with an internal resistance of 23 Ohm. Moreover, these cells demonstrated thermal stability during both charging and discharging processes, which can be attributed to the concentration and quality of the ionic species. Furthermore, the surfaces of the Titanium electrodes were examined using FESEM and EDXA equipment to assess the impact of the ionic liquid and DES on these electrodes.